Middle age knowledge regarding health screening - A.I. Alaa sabah Ghazal (Genius Journals, 2023)
A descriptive analytical study was carried out to assess the middle age knowledge regarding health screening, who attending outpatient clinic for seeking treatment at Baghdad General Teaching Hospital.
Keywords: Middle age; knowledge